A liberdade em Polanyi - Baptista, António (The concept of freedom in Polanyi., 2018)
Karl Polanyi's The Great Transformation is a powerful criticism of free market ideology and its intrinsic assumptions that is based on an implicit political theory of freedom. The attempt is made here of reconstructing and making explicit Polanyi's concept of "freedom in a complex society" in light of his commitment to a sui generis form of socialism and his lifelong opposition to arguments as found typically in Friedrich Hayek's The Road to Serfdom. (English)
Political Science
Keywords: Hayek; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; Road to Serfdom (book); degrees of freedom; democracia; democracy; freedom; freedom in a complex society; liberdade; planificação; planning; socialism; socialismo; transformative learning

Desenvolvimento territorial no Brasil: uma análise a partir da concepção teórica de Karl Polanyi - Waldecy Rodrigues; Nayara Silva Santos (Desarrollo territorial en Brasil: un análisis desde Karl Polanyi., 2018)
This paper analyzes the municipal development in Brazil from the theoretical design of Karl Polanyi. Methodologically, the Polanyi's city development index of Polanyi (IDMP). The results show that according to the concepts analyzed, the Brazilian municipalities, in their majority, have multidimensional incipient features and that there is a direct positive relationship between economic pluralism and quality of life levels. (English)
Development Studies
Keywords: Brazil; abordagem multidimensional; approche multídimensionnelle; city development; desarrollo; desarrollo municipal; desenvolvimento; desenvolvimento municipal; development; developpement; developpement des municipalites; economia plural; economía diversa; enfoque multidimensional; multidimensional approach; plural economy; économie plurielle

Polanyi e Granovetter a partir do olhar de Lukacs. (Polanyi and Granovetter from Lukacs Glance. With English summary.) - de Araujo, Paulo Henrique Furtado (Economica (Fluminense Federal University), 2015)
The article critically examines the contributions of Polanyi and Granovetter on the embeddedness notions and functioning of any individual in social networks from the construction proposed by Lukacs in "The Ontology of Social Being". It is proposed to rethink and point clues to an explanation, consistent with the Marxian thought, the necessary links between the decision-making done in the here and now, in the quotidian of world of men, and the legalities and more general trends produced by them and felt by the entire social being.
Economics
Keywords: GRANOVETTER; Mark; LUKACS; Georg; Marxian; Sraffian; current heterodox approaches: socialist; economic anthropology; economic sociology; history of economic thought: individuals; language; social and economic stratification

A crise de legitimidade da governança climática global. Combinação de uma perspetiva marxista e polanyiana - Van Vossole, Jonas (2013)
This article frames recent problems of the RIO+20 summit, the failure of the Copenhagen Climate Change Conference (COP15) and the problems of the carbon markets within a broader legitimacy crisis of global governance, consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between the Marx-type of contestation, referring to emerging classes/states, and the Polanyi-type of contestation, referring to the victims of global mercantilization. In the case of climate governance, these winners and losers are represented by BRICS in climate negotiations and by the global environmental justice movement. (English)
Political Science
Keywords: RIO+20; United Nations Conference on Sustainable Development (2012 : Rio de Janeiro; Brazil); capitalism; capitalisme; capitalismo; carbon dioxide mitigation; environmental aspects; environmental justice; gouvernance; governance; governança; international cooperation; international cooperation on climate change; international cooperation on environmental justice; international cooperation on environmental policy; justice environnementale; justiça ambiental; legitimacy; legitimation (sociology); legitimidade; légitimité

A contribuição de Karl Polanyi para a sociologia do desenvolvimento rural - Schneider, Sergio; Escher, Fabiano (Sociologias, 2011)
O ensaio aborda a importância da redescoberta do pensamento de Karl Polanyi e de sua crítica à "sociedade de mercado" na retomada dos estudos e debates sobre o desenvolvimento (rural). Após uma apresentação geral do quadro teórico e analítico de Polanyi, buscamos utilizar seus conceitos para interpretar a dinâmica da mercantilização dos meios de vida e das formas sociais de trabalho e produção no espaço rural, bem como dos sistemas agroalimentares no capitalismo contemporâneo. Com base nestas proposições, refletimos sobre o papel dos atores sociais e das instituições nos processos de mudança social em geral e os de desenvolvimento rural em particular. Finalizamos, propondo algumas potencialidades dessa abordagem para os estudos sobre desenvolvimento rural no Brasil. ENG: The essay deals with the importance of the rediscovery of Karl Polanyi's thinking and of his criticism of the "market society" in resuming (rural) development studies and debates. Following an overall presentation of Polanyi's theoretical and analytical framework, we look for using his concepts to interpret the commoditization dynamics of the rural livelihoods and the social forms of labor and production in the rural space, as well as the commoditization of the agri-food systems in the contemporary capitalism. Based on these statements, we reflect about the role of social actors and institutions in the processes of social change at large and of rural development in particular. And, finally, we propose some potentialities of this approach for the rural development studies in Brazil.
Sociology; Economics
Keywords: commoditization; institutions; rural development; social actors